Positional uncertainty of network RTK observations in a modern datum - Bernstein T. (Sciendo, 2021)
The Geocentric Datum of Australia 2020 (GDA2020) is Australia’s new and much improved national datum. It is based on a single, nationwide least squares network adjustment that rigorously propagates uncertainty. This paper explores three options to include Network Real-Time Kinematic (NRTK) observations and their Positional Uncertainty (PU) in the survey control network of New South Wales (NSW) via the GDA2020 state adjustment. In the first option, PU is empirically estimated based on a dataset of more than 1,500 observations to obtain values that can be uniformly applied to all NRTK observations. In the second option, PU is calculated for each NRTK observation, based on the coordinate quality indicators provided by the Global Navigation Satellite System (GNSS) equipment. Both options continue to treat NRTK observations as point-based position solutions, resulting in poor correlation with surrounding survey control marks. The third option overcomes this issue by utilising the automatically computed GNSS baselines between NRTK observations and their Virtual Reference Station (VRS) to create a connected network that can be adjusted like a static GNSS network. Using a typical urban NRTK survey in Sydney as an example, it is shown that this method offers a rigorous computation of PU, while maintaining the quick and easy nature of NRTK positioning.